Personalized Cancer Vaccine Platform for Clinically Relevant Oncolytic Enveloped Viruses - Erkko Ylösmäki; Cristina Malorzo; Cristian Capasso; Oona Honkasalo; Manlio Fusciello; Beatriz Martins; Leena Ylösmäki; Antti Louna; Sara Feola; Henrik Paavilainen; Karita Peltonen; Veijo Hukkanen; et al. (2018)
The approval of the first oncolytic virus for the treatment of metastatic melanoma and the compiling evidence that the use of oncolytic viruses can enhance cancer immunotherapies targeted against various immune checkpoint proteins has attracted great interest in the field of cancer virotherapy. We have developed a novel platform for clinically relevant enveloped viruses that can direct the virus-induced immune response against tumor antigens. By physically attaching tumor-specific peptides onto the viral envelope of vaccinia virus and herpes simplex virus 1 (HSV-1), we were able to induce a strong T cell-specific immune response toward these tumor antigens. These therapeutic peptides could be attached onto the viral envelope by using a cell-penetrating peptide sequence derived from human immunodeficiency virus Tat N-terminally fused to the tumor-specific peptides or, alternatively, therapeutic peptides could be conjugated with cholesterol for the attachment of the peptides onto the viral envelope. We used two mouse models of melanoma termed B16.OVA and B16-F10 for testing the efficacy of OVA SIINFEKL-peptide-coated viruses and gp100-Trp2-peptide-coated viruses, respectively, and show that by coating the viral envelope with therapeutic peptides, the anti-tumor immunity and the number of tumor-specific CD8+ T cells in the tumor microenvironment can be significantly enhanced.